Is it really better to give than to receive? (Not if your friends know where to shop!) - Stephen R. Palmquist (اخلاق وحیانی, 2015)
The common saying, “it is better to give than to receive”, is so widespread that its truth is often merely assumed. But can this maxim withstand a careful analysis? The relevant concepts (“giving”, “receiving”, and “better”) can be interpreted in too many ways to discuss thoroughly in a single essay. Instead, this essay classifies the various ways of interpreting the distinction between giving and receiving, then explores in depth one of the options, based on a pivotal distinction between active and passive types of both giving and receiving. I defend the controversial claim that there is at least one important sense (arguably the most important, for ethical purposes) in which it is not better to give than receive, but precisely the opposite. Indeed, the survival of the human race may depend on our willingness to receive.